Control chart: A statistical process control tool in pharmacy - Shah, Samip; Shridhar, Pandya; Gohil, Dipti (Asian Journal of Pharmaceutics (AJP), 2014)
Control chart is the most successful statistical process control (SPC) tool, originally developed by Walter Shewhart in the early 1920s. A control chart can easily collect, organize and store information, calculate answers and present results in easy to understand graphs. It helps to record data and allows to see when an unusual event, e.g., a very high or low observation compared with â€œtypicalâ€ process performance, occurs. Computers accept information typed in manually, read from scanners or manufacturing machines, or imported from other computer databases.The resulting control charts can be examined in greater detail, incorporated into reports, or sent across the internet. A stable process is a basic requirement for process improvement efforts. A computer collecting information in real time can even detect very slight changes in a process, and even warn you in time to prevent process errors before they occur. First, control charts demonstrate how consistently process is performing, and whether you should, or should not, attempt to adjust it. Next, the statistical process control chart compares the process performance to standard pharmaceutical requirements, providing a process capability index as an ongoing, accurate direction for quality improvement. Finally, control charts and its resulting process capability index quickly evaluate the results of quality initiatives designed to improve process consistency. This review focuses on elements of control chart and types of various control charts along with example. Advantages of various control charts are also included.